The Carbon Footprint of Games Distribution. (1st September 2014) - Mayers, Kieren; Koomey, Jonathan; Hall, Rebecca; Bauer, Maria; France, Chris; Webb, Amanda
Summary This research investigates the carbon footprint of the lifecycle of console games, using the example of PlayStation®3 distribution in the UK. We estimate total carbon equivalent emissions for an average 8.8‐gigabyte (GB) game based on data for 2010. The bulk of emissions are accounted for by game play, followed by production and distribution. Two delivery scenarios are compared: The first examines Blu‐ray discs (BDs) delivered by retail stores, and the second, games files downloaded over broadband Internet. Contrary to findings in previous research on music distribution, distribution of games by physical BDs results in lower greenhouse gas emissions than by Internet download. The estimated carbon emissions from downloading only fall definitively below that of BDs for games smaller than 1.3 GB. Sensitivity analysis indicates that as average game file sizes increase, and the energy intensity of the Internet falls, the file size at which BDs would result in lower emissions than downloads could shift either up‐ or downward over the next few years. Overall, the results appear to be broadly applicable to title games within the European Union (EU), and for larger‐than‐average sized games in the United States. Further research would be needed to confirm whether similar findings would apply in future years with changes in game size and Internet efficiency. The study findings serve to illustrate why it is not always true that digital distribution of media will have lower carbon emissions than distribution by physical means when file sizes are large.